Pelatihan pembuatan perpustakaan online berbasis EndNote program pada penulisan karya ilmiah - Sultan Baa; Haryanto Haryanto; Mardiyanah Nasta (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
English Education Study Program is one of the study programs within the English Department of UNM. As one of the lecturers who taught Writing IV subject for the Semester IV students of English Department of UNM, I found that many students still have lack ability to write reference style correctly and precisely. In order to overcome this problem, it was needed a training for these students in improving their knowledge and skills in the area by using referencing software. The purpose of the training was to improve the students’ ability in making online library by using reference software called EndNote Program and be able to apply in writing references or bibliography in academic writing. The training was conducted for four weeks during May-June 2019. The methods used in this training were presentation and simulation. The assessments were conducted after the training using observation sheets. The results of the test indicated that the majority of the participants improved their ability in making online library and could use EndNote Program in writing their references.  Considering the benefits of the program and the high motivation of the participants, it is recommended that similar training should be carried out to other students in this study program.